The UK's modern slavery legislation: an early assessment of progress - Craig, Gary (2017)
In 2015, the Westminster UK government introduced a Modern Slavery Act described by its proponents as "world-leading". This description was challenged at the time both inside and outside the UK. Two years on, it is possible to make a preliminary assessment of progress with the Act and its two counterparts in Scotland and Northern Ireland. This article reviews the origins of discussions about modern slavery in the UK, describes the process leading to the passage of the Modern Slavery Act(s) and attempts an early evaluation of its effectiveness. It concludes that much remains to be done to ensure that they achieve their goal of abolishing slavery in the UK.